Faecal occult blood testing screening for colorectal cancer and 'missed' interval cancers: are we ignoring the elephant in the room? Results of a multicentre study. (May 2017) - George, A. T.; Aggarwal, S.; Dharmavaram, S.; Menon, A.; Dube, M.; Vogler, M.; Field, A.
Abstract: Aim: Biennial faecal occult blood testing (FOBT) is used to screen for colorectal cancer throughout the UK. Interval cancers are tumours that develop in patients between screening rounds who have had a negative FOBT. Through a multicentre study, we compared the demographics of patients with interval cancers, FOBT screen detected cancers and cancers that developed in patients who chose not to participate in the screening programme. Method: Five hundred and sixteen colorectal cancers were detected in the screening age group (60–74 years) population in three UK National Health Service hospitals over 2 years. One hundred and twenty seven (25%) were interval cancers, 161 (31%) were screen detected and 228 (44%) were cancers that developed in patients who had declined FOBT. The interval cancer group had a higher incidence of right‐sided cancers (38% vs 29% and 24%), a higher proportion of high tumour stages (Dukes C and D) (70% vs 53% and 33%) and a shorter time from diagnosis to death (10 months vs 13 months and 24 months) compared to patients who had declined the FOBT and the FOBT screen detected cancers. Of all the patients studied, those with right‐sided interval cancers had the worst outcome. Conclusion: A quarter of the colorectal cancers diagnosed in our study were interval cancers. Patients with right‐sided interval cancers had the highest proportion of Dukes C and D tumours coupled with the shortest survival time after diagnosis compared with the other groups.